Strategic operations framework for disassembly in remanufacturing - Anjar Priyono; Winifred L. Ijomah; Umit S. Bititci (Journal of Remanufacturing, 2015)
Studies on disassembly for remanufacturing using strategic perspectives have been overlooked in current studies. This research uses a strategic approach to examine how product, process and organisational designs affect disassembly strategies for different remanufacturer types. Three companies consisting of two automotive and one jet engine remanufacturer were selected as subjects. A case study approach using qualitative data was adopted to examine how remanufacturers design their disassembly strategies. The analysis revealed that the two major factors influencing disassembly strategies are product complexity and the stability of core supply. It also determined and grouped the factors that affect disassembly within remanufacturing.
Keywords: 650; Disassembly; Strategy; Remanufacturing; Factors; Uncertainty